WORM INFECTION AMONG SCHOOL CHILDREN OF UNIVERSITY OF PESHAWAR - Attaullah, Shahnaz; Khan, Bilal Hassan (Journal of Postgraduate Medical Institute, 2016)
Objective: To find out the pattern of worm infection among school children of University of Peshawar. Methodology: A total of 253 school children (male 137 and female 116) from three different schools of University of Peshawar were randomly selected. Worm infection of stool specimens from school children of University of Peshawar were investigated through standard methods during September, 2013 to February, 2014. The data were analyzed with standard statistical procedures using SPSS version 16, frequency and percentages were computed for all variables. Results were presented in the form of tables. Results: The overall infection rate was 23.7%, of which 10 % showed mixed infection. Among positive cases Ascaris lumbricoides was the commonest (38.3 %), followed by Hymenolepis nana (15 %), Entamoeba coli (11. 7) %, Giardia lamblia (10) % and Entamoeba histolytica in 5 % cases. The prevalence rate for Taenia saginata and Enterobius vermicularis were 3.3 % and 1. 7 %, while Trichurus trichiura and Ancylostoma duodenale were found in 1. 7 % and 3.3% cases respectively. Conclusion: Worm infection was found in a significant number of school children of University of Peshawar. Ascaris lumbricoides was the commonest worm infection.